The Relationship Between Insecure Attachment and Emotional Dependence in Romantic Relationships in Early Adulthood - Putri, Nurul Adillah; Gina, Fathana (PROMOTOR, 2025)
This study aims to explore the relationship between insecure attachment and emotional dependence in romantic relationships in early adulthood. This quantitative study used convenience sampling method as the sampling process. Participants in this study were early adults in the age range of 18-25 years old who have been and or are in romantic relationships with a total of 150 participants. The measuring instrument used to measure insecure attachment uses the Indonesian version of the Experiences in Close Relationships-Revised (ECR-R) measuring instrument and emotional dependence is measured using the Emotional Dependence Questionnaire (EDQ). The results of data analysis show that there is a positive correlation between anxiety attachment and emotional dependence, while avoidant attachment shows a negative correlation to emotional dependence. The findings of these results are expected to provide new insights into the psychological dynamics in romantic relationships, especially in the context of insecure attachment patterns.